[(18)F]fallypride characterization of striatal and extrastriatal D(2/3) receptors in Parkinson's disease - Stark, Adam J. (Neuroimage Clin, 2018)
Parkinson's disease (PD) is characterized by widespread degeneration of monoaminergic (especially dopaminergic) networks, manifesting with a number of both motor and non-motor symptoms. Regional alterations to dopamine D(2/3) receptors in PD patients are documented in striatal and some extrastriatal areas, and medications that target D(2/3) receptors can improve motor and non-motor symptoms. However, data regarding the combined pattern of D(2/3) receptor binding in both striatal and extrastriatal regions in PD are limited. We studied 35 PD patients off-medication and 31 age- and sex-matched healthy controls (HCs) using PET imaging with [(18)F]fallypride, a high affinity D(2/3) receptor ligand, to measure striatal and extrastriatal D(2/3) nondisplaceable binding potential (BP(ND)). PD patients completed PET imaging in the off medication state, and motor severity was concurrently assessed. Voxel-wise evaluation between groups revealed significant BP(ND) reductions in PD patients in striatal and several extrastriatal regions, including the locus coeruleus and mesotemporal cortex. A region-of-interest (ROI) based approach quantified differences in dopamine D(2/3) receptors, where reduced BP(ND) was noted in the globus pallidus, caudate, amygdala, hippocampus, ventral midbrain, and thalamus of PD patients relative to HC subjects. Motor severity positively correlated with D(2/3) receptor density in the putamen and globus pallidus. These findings support the hypothesis that abnormal D(2/3) expression occurs in regions related to both the motor and non-motor symptoms of PD, including areas richly invested with noradrenergic neurons.